2000
DOI: 10.1080/07315724.2000.10718083
|View full text |Cite
|
Sign up to set email alerts
|

The Bioavailability of Dietary Calcium

Abstract: This update focuses on the bioavailability of dietary calcium for humans. Fundamentals of calcium metabolism, intestinal absorption, urinary excretion and balance are recalled. Dietary factors, especially lactose and other milk components, influencing calcium bioavailability at intestinal and renal levels are reviewed. A critical examination of all the methods used for evaluating calcium bioavailability is made. This includes in vitro assays, classical and isotopic balances, urinary excretion, isotope labeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
281
2
33

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 448 publications
(331 citation statements)
references
References 128 publications
3
281
2
33
Order By: Relevance
“…One way to do this would be to build on this study's foundation using radiolabelled CaOx to definitively determine if it is being incorporated into the bone matrix and therefore being utilised, and also to use metabolic cages to accurately record intake and excrement of calcium (Guéguen & Pointillart, 2000). Metabolic cages facilitate the collection of all urine and faeces produced by an individual, the analysis of which would indicate the extent to which CaOx passes through the animal unutilised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to do this would be to build on this study's foundation using radiolabelled CaOx to definitively determine if it is being incorporated into the bone matrix and therefore being utilised, and also to use metabolic cages to accurately record intake and excrement of calcium (Guéguen & Pointillart, 2000). Metabolic cages facilitate the collection of all urine and faeces produced by an individual, the analysis of which would indicate the extent to which CaOx passes through the animal unutilised.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, individuals maintained on a diet in which the main source of calcium is CaOx will likely undergo increased bone resorption and reduced BMD if calcium is not being absorbed, when compared with individuals on a normal skeletal maintenance diet. Measuring bone parameters after prolonged exposure to treatment diet are a reliable way of estimating the long‐term effects of different calcium intakes in humans and rats (Guéguen & Pointillart, 2000). …”
Section: Introductionmentioning
confidence: 99%
“…Contudo, produtos lácteos não fazem parte da dieta habitual de adolescentes, adultos e idosos, em proporções suficientes para alcançar essas recomendações 13,18,20,30 . No caso de adolescentes e idosos, seriam necessárias pelo menos cinco porções diárias de leite e derivados para se atingir a AI 21 , o que acarretaria desequilíbrio na ingestão de macronutrientes, em razão da excessiva ingestão protéica que, por sua vez, poderia induzir a um aumento na excreção renal de cálcio 8 . Assim, a ingestão de alimentos de consumo habitual enriquecidos com o pó da casca de ovo pode contribuir para a ingestão adequada de cálcio sem comprometer a qualidade nutricional da dieta.…”
Section: Análise Comparativa Do Teor De Cálcio Das Formulações Fortifunclassified
“…Estudos descritivos conduzidos em vários países mostram um consumo de cálcio inadequado, muitas vezes abaixo de 50% da ingestão preconizada 7,13,20 . Outros fatores contribuem para o agravamento dessa situação de aporte inadequado de cálcio, como a presença de fitatos na dieta e o consumo elevado de proteínas, que podem reduzir a biodisponibilidade do mineral 8 .…”
Section: Introductionunclassified
“…Several studies have demonstrated the importance of considering both food groups and the overall diet in assessing their impact on bone health, which may partially explain the relationship between nutrient intake and bone mineral acquisition in children and adolescents (Heaney, 2004;Seiquer et al, 2008). Milk and dairy products contribute around 70% of total dietary calcium and thus, they are by far the main source of calcium in Western diets (Guéguen & Pointillart, 2000). Addition of these products to the adolescent's diet is the best strategy to meet calcium recommendations and to achieve optimal bone mineralization (Cadogan et al, 1997).…”
Section: Calciummentioning
confidence: 99%